Estudo Fitoquímico de Croton Jacobinensis Baill (Euphorbiaceae) - Silva, Francisco José Souza da (2010)
SILVA, F. J. S. Estudo Fitoquímico de Croton Jacobinensis Baill (Euphorbiaceae). 2010. 116 f. Dissertação (Mestrado em Química Orgânica) - Centro de Ciências, Universidade Federal do Ceará, Fortaleza, 2010.